2010
DOI: 10.1093/europace/euq333
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive continuous blood pressure monitoring of tachycardic episodes during interventional electrophysiology

Abstract: AimsWe thought to evaluate feasibility of continuous non-invasive blood pressure monitoring during procedures of interventional electrophysiology.Methods and resultsWe evaluated continuous non-invasive finger blood pressure (BP) monitoring by means of the Nexfin device in 22 patients (mean age 70 ± 24 years), undergoing procedures of interventional electrophysiology, in critical situations of hypotension caused by tachyarrhythmias or by intermittent incremental ventricular temporary pacing till to the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…There is a study, using systemic vasoactive drugs, suggesting that regional vascular tone may not be a significant contributing factor to the results obtained by this technology [42]. Secondly, although many studies have validated the Finapres technology used by Nexfin compared to standard auscultatory sphygmomanometry and intra-arterial catheterization in different populations [14,[16][17][18][19][20][21], our study showed a significant mean percent error with Bland-Altman analysis between the SBP NXF compared to SBP CUFF as well as a concordance of only 81.3%. With the new method described by Critchley et al, primarily for cardiac output monitor trending, the authors recommend a mean polar angle or angular bias of less than ±5°and radial limits of agreement less than ±30°in order for a device to display good trending ability [26].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a study, using systemic vasoactive drugs, suggesting that regional vascular tone may not be a significant contributing factor to the results obtained by this technology [42]. Secondly, although many studies have validated the Finapres technology used by Nexfin compared to standard auscultatory sphygmomanometry and intra-arterial catheterization in different populations [14,[16][17][18][19][20][21], our study showed a significant mean percent error with Bland-Altman analysis between the SBP NXF compared to SBP CUFF as well as a concordance of only 81.3%. With the new method described by Critchley et al, primarily for cardiac output monitor trending, the authors recommend a mean polar angle or angular bias of less than ±5°and radial limits of agreement less than ±30°in order for a device to display good trending ability [26].…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the Nexfin device provides cardiac output values calculated based on a pulse contour analysis method described by Bogert et al [15]. The Nexfin has been well-validatedto non-invasivelyand continuously monitor arterial pressures [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The Nexfin has been quite largely validated for measuring arterial pressure [4-10]. However, its reliability to measure cardiac index (CI) has been mainly investigated in non-critically ill patients [5,11-15].…”
Section: Introductionmentioning
confidence: 99%
“…During such procedures Nexfin recorded reliable BP waveforms notwithstanding the presence of tachyarrhythmia [114]. The authors stated that continuous noninvasive BP monitoring is feasible in the interventional electrophysiology laboratory and may replace intra-arterial BP in that setting.…”
Section: Clinical Applications Of Noninvasive Continuous Hemodynamic mentioning
confidence: 99%